Allopregnanolone pleiotropic action in neurons and astrocytes: calcium signaling as a unifying mechanism - Wang, Tian; Chen, Shuhua; Mao, Zisu; Shang, Yuan; Brinton, Roberta Diaz (Frontiers in Endocrinology, 2023)
Allopregnanolone (Allo) is a neurosteroid with pleiotropic action in the brain that includes neurogenesis, oligogenesis, human and rodent neural stem cell regeneration, increased glucose metabolism, mitochondrial respiration and biogenesis, improved cognitive function, and reduction of both inflammation and Alzheimer's (AD) pathology. Because the breadth of Allo-induced responses requires activation of multiple systems of biology in the absence of an Allo-specific nuclear receptor, analyses were conducted in both neurons and astrocytes to identify unifying systems and signaling pathways.Mechanisms of Allo action were investigated in embryonic hippocampal neurons and astrocytes cultured in an Aging Model (AM) media. Cellular morphology, mitochondrial function, and transcriptomics were investigated followed by mechanistic pathway analyses.In hippocampal neurons, Allo significantly increased neurite outgrowth and synaptic protein expression, which were paralleled by upregulated synaptogenesis and long-term potentiation gene expression profiles. Mechanistically, Allo induced Ca 2+ /CREB signaling cascades. In parallel, Allo significantly increased maximal mitochondrial respiration, mitochondrial membrane potential, and Complex IV activity while reducing oxidative stress, which required both the GABAA and L-type Ca 2+ channels. In astrocytes, Allo increased ATP generation, mitochondrial function and dynamics while reducing oxidative stress, inflammasome indicators, and apoptotic signaling. Mechanistically, Allo regulation of astrocytic mitochondrial function required both the GABAA and L-type Ca 2+ channels. Further, Allo activated NRF1-TFAM signaling and increased the DRP1/OPA1 protein ratio, which led to increased mitochondrial biogenesis and dynamics.Collectively, the cellular, mitochondrial, transcriptional, and pharmacological profiles provide evidence in support of calcium signaling as a unifying mechanism for Allo pleiotropic actions in the brain.